Comparison of Different Manufacturing Processes of AISI 4140 Steel with Regard to Surface Modification and Its Influencing Depth - Florian Borchers; Brigitte Clausen; Sandro Eckert; Lisa Ehle; Jeremy Epp; Simon Harst; Matthias Hettig; Andreas Klink; Ewald Kohls; Heiner Meyer; Markus Meurer; Bob Rommes; et al. (Metals, 2020)
The surface and subsurface conditions of components are significant for their functional properties. Every manufacturing process step changes the surface condition due to its mechanical, chemical and/or thermal impact. The depth of the affected zone varies for different machining operations, and is predetermined by the process parameters and characteristics. Furthermore, the initial state has a decisive influence on the interactions that lead to the final surface conditions. The aim of the investigation presented here is to compare the influence of the load characteristics over the depth applied to manufactured components by several different machining operations and to determine the causing mechanisms. In order to ensure better comparability between the surface modifications caused by different machining operations, the same material was used (AISI 4140; German steel grade 42CrMo4 acc. to DIN EN 10083-3) and annealed to a ferritic-pearlitic microstructure. Based on interdisciplinary cooperation within the collaborative research center CRC/Transregio 136 “Process Signatures”, seven different manufacturing processes, i.e., grinding, turning, deep rolling, laser processing, inductive heat treatment, electrical discharge machining (EDM) and electrochemical machining (ECM), were used, and the resulting surface zones were investigated by highly specialized analysis techniques. This work presents the results of X-ray measurements, hardness measurements and electron microscopic investigations. As a result, the characteristics and depths of the material modifications, as well as their underlying mechanisms and causes, were studied. Mechanisms occurring within 42CrMo4 steel due to thermal, mechanical, chemical or mixed impacts were identified as phase transformation, solidification and strengthening due to dislocation generation and accumulation, continuum dynamic recrystallization and dynamic recovery, as well as chemical reactions.